THE INFLUENCE OF CORPORATE GOVERNANCE ON THE QUALITY OF FINANCIAL REPORTING - Jauhar Muammar Qadhafie (GLOBAL RESEARCH IN ECONOMICS AND ADVANCE THEORY (GREAT), 2025)
This study examines the influence of corporate governance on the quality of financial reporting, emphasizing the importance of transparency, accountability, and integrity in sustaining stakeholder trust. The research is motivated by the pivotal role of financial statements in investment decision-making and the growing demand for effective governance frameworks, particularly in the aftermath of global crises such as the financial downturns and the COVID-19 pandemic. A quantitative approach was employed, focusing on S&P 500 companies. From this population, a stratified random sample of 150 firms was selected to ensure representation across industries and governance structures. Data were collected through surveys of governance officers and financial reporting managers, supplemented by archival sources including annual reports, financial statements, and governance ratings. Regression and correlation analyses were conducted using SPSS and R to assess the relationship between governance mechanisms and reporting quality. The findings reveal a strong positive correlation between the Corporate Governance Index (CGI) and financial reporting quality (r = 0.68, p < 0.01). Firms with higher governance scores, characterized by board independence and effective audit committees, demonstrated more accurate, transparent, and timely reporting, while also experiencing fewer financial restatements. The practical implications highlight the need for organizations to enhance board evaluations, increase the proportion of independent directors, and strengthen audit committee functions to achieve reliable reporting. Limitations of this study include its focus on U.S.-based companies and reliance on secondary data, suggesting that future research should incorporate cross-country comparisons, cultural perspectives, and emerging technologies such as blockchain and artificial intelligence. Overall, the results underscore that effective corporate governance serves as a cornerstone for high-quality financial reporting, fostering investor confidence, reducing compliance risks, and supporting long-term corporate sustainability.